Pengaruh Penggunaan Media Audiovisual Terhadap Hasil Belajar Menulis Puisi Makassar Siswa - Mitaliana Mitaliana; Kembong Daeng; Hajrah Hajrah (INSIGHT: Indonesian Journal Social Studies and Humanities, 2021)
Abstract. The study was to describe the impact audiovisual media may have on the results of learning to write eighth-grade eighth - year class of class 1 Tarowang district of Jeneponto. The research is quantitative. The population in the study has a total of 140 eighth graders in five classes. In this study, random sampling researchers. The study is an experimental study conducted four times, namely observation, pretest (before experiment), action, and posttest activities (after experiments) and the results are influential before audiovisual media use and after audiovisual media use by focusing the two classes used as samples, namely, VIII A and VIII B. It is evident that the effect of audiovisual media use on the results of learning to write Makassar poems after the use of audiovisual class VIII students 1 Tarowang district of Jeneponto indicated by a score of 75-100 students or 94.82%. Meanwhile, the 0-75 student scores 3 The impact of audiovisual media use on the results of learning to write poems at junior high school l 1 Tarowang district Jeneponto points out that significant value is 0,000 less than 0.05 (0,000< 0.05), hence the hypothesis in the study is stated to be accepted. This means that the variable use of audiovisual media is positive for the results of learning to write Makassar, seventh year student Tarowang of the Jeneponto district, there is a significant influence between students' learning to write Makassar poems before media use and after audiovisual media use in seventh year's seventh year students. Keywords: composer of media, audiovisual, to the results of learning to write Makassar poetry.